PROFESIONALISME DAN BUDAYA ORGANISASI SERTA PENGARUHNYA TERHADAP KINERJA KARYAWAN GRAGE HOTEL KOTA BENGKULU - Fauzan Fauzan (Universitas Prof. Dr. Hazairin SH, 2020)
This research is an explanatory study, because it sees the relationship between the variables ofprofessionalism (X1) and organizational culture (X2) with the employee performance variable(Y) as well as hypothesis testing. The problem raised is how much influence professionalism andorganizational culture have on employee performance at Grage Hotel Bengkulu. In general, thisstudy aims to assist government programs in promoting tourism in Indonesia including all itsderivatives, specifically the purpose of this study is (1). participate in promoting tourism,especially hotels in Bengkulu Province. (2) Provide input to Grage Hotel Bengkulu in improvingemployee performance. The data used in this study are quantitative data obtained from theresults of distributing questionnaires to 65 respondents, then processed into statistical analysis.Based on the results of data analysis, it can be concluded that (1) the professionalism variable(X1) organizational culture (X2) has a significant effect on employee performance (Y). Thisinformation can be seen from the regression equation, multiple correlation, determination, t-testand f-test. (2) The contribution of the two variables to employee performance is almost the same.As a suggestion, professionalism and organizational culture need to be developed.